STUDY OF PHYTASE, PHYTATE AND PROTEIN PROFILING IN INDIAN WHEAT VARIETIES - MANISH KUMAR; SUSHMA (International Journal of Pharma and Bio Sciences, 2015)
In the present study phytase, phytate and protein content were determined in twenty wheat varieties. Among twenty wheat varieties, LOK-1 variety was found to have higher content of phytase, phytate and protein. During the study, phytase activity was 197.30±0.65 to 2132.77±0.29 nM/min/g, phytate 2.90±0.35 to 7.07±0.09 and protein 77.07±0.64 to 148.40±0.31 mg/g found, respectively through different processed wheat varieties; soaking, germination, kilning, heating and grinding under present study.